Novel 4-Chromanone-Derived Compounds as Plant Immunity Inducers against CMV Disease in Passiflora spp. (Passion Fruit) - Tianli Wu; Lu Yu; Lingling Xiao; Tao Wang; Pei Li; Bo Mu (Molecules, 2024)
This study involved the design and synthesis of a series of novel 4-chromanone-derived compounds. Their in vivo anti-cucumber mosaic virus (CMV) activity in field trials against CMV disease in Passiflora spp. was then assessed. Bioassay results demonstrated that compounds 7c and 7g exhibited remarkable curative effects and protection against CMV, with inhibition rates of 57.69% and 51.73% and 56.13% and 52.39%, respectively, surpassing those of dufulin and comparable to ningnanmycin. Field trials results indicated that compound 7c displayed significant efficacy against CMV disease in Passiflora spp. (passion fruit) after the third spraying at a concentration of 200 mg/L, with a relative control efficiency of 47.49%, surpassing that of dufulin and comparable to ningnanmycin. Meanwhile, nutritional quality test results revealed that compound 7c effectively enhanced the disease resistance of Passiflora spp., as evidenced by significant increases in soluble protein, soluble sugar, total phenol, and chlorophyll contents in Passiflora spp. leaves as well as improved the flavor and taste of Passiflora spp. fruits, as demonstrated by notable increases in soluble protein, soluble sugar, soluble solid, and vitamin C contents in Passiflora spp. fruits. Additionally, a transcriptome analysis revealed that compound 7c primarily targeted the abscisic acid (ABA) signaling pathway, a crucial plant hormone signal transduction pathway, thereby augmenting resistance against CMV disease in Passiflora spp. Therefore, this study demonstrates the potential application of these novel 4-chromanone-derived compounds as effective inducers of plant immunity for controlling CMV disease in Passiflora spp. in the coming decades.